Management of Religious Preservation Program Activities (Hifz Al-Din) at SMA Plus Al-Azhar Jember - Farid, Miftah; Widodo, Sembodo Ardi; Baldani, Moch. Ayyub Sholah; Septi, Asri Dwika (Sunan Kalijaga International Journal on Islamic Educational Research, 2026)
This study aims to analyze how the ḥifẓ al-dīn program is designed, implemented, and interpreted in realizing the motto of SMA Plus Al-Azhar Jember. The study addresses the need to understand ḥifẓ al-dīn not only as a normative concept within Maqāṣid al-Sharī‘ah, but also as a managerial framework for organizing school-based religious formation. Its key argument is that religious preservation becomes educationally meaningful when it is institutionalized through structured programs, daily habituation, and character-building activities. This study employed qualitative field research with a phenomenological orientation. Data were collected through two in-depth interview sessions with the principal on 24 April 2025 and 27 April 2025, supported by field observations of routine religious activities and documentation of school programs. The data were analyzed through reduction, display, and conclusion drawing, while credibility was strengthened through methodological triangulation and member checking. The findings show that the ḥifẓ al-dīn program is managed through two main orientations: strengthening students’ spirituality and forming Islamic character. Spiritual strengthening is reflected in Asmā’ al-Ḥusnā recitation, Qur’anic tadarus, Shalawat Nariyah, Duha prayer, congregational prayers, and Rohis activities. Islamic character formation is developed through leadership training, digital da‘wah, and Ta’lim Senin. These programs shape three main expressions in students’ daily lives: worship, adab, and achievement orientation. The study contributes to Islamic education scholarship by positioning ḥifẓ al-dīn as a practical framework for religious program management. However, because this study was limited to one school and one key informant, future research should involve broader participants and comparative school contexts.